Sistem Pendukung Keputusan Pemilihan Sekretaris Daerah Menggunakan Metode MOORA (Studi Kasus: Kantor Bupati Karo) - Malau, Resli Agustina (STMIK Budi Darma, 2019)
The selection of regional secretaries, has problems, namely the system of selecting regional secretaries occurs, there are elements of superior officials and proximity or reciprocal political services, and it is often found that there is an alleged bribery process so that the regional secretary chosen is not as expected. To overcome this problem, a Decision Support System is needed by using the MOORA method (Multi Objective Optimization On The Base Of Ratio Analysis) which can assist the Office of the Karo Regent in selecting regional secretaries. With the adoption of a decision support system using the MOORA method simplifies and speeds up the process of selecting regional secretaries. So that the selection of regional secretaries is more effective and efficient.